The Effect of Service Quality on Patient Satisfaction at King Faisal Hospital in Saudi Arabia - Alabbas, Anood Matooq; Alzahrani, Faisal Essa; Alsulami, Ahmed Amer; Almogati, Mohammed Wasl; Alhutayrashi, Yaseer Saeed; Althobaiti, Abdulrahim Sharaf; Alotaibi, Moshari Mansour; Alotaibi, Mufreh Aali; Alofi, Adil Saleh; Alsarawani, Talal Meshal; Alotaibi, Ahmed Nawwar; Allehyani, Maher Mohammed; et al. (Journal of Ecohumanism, 2024)
The healthcare sector offers medical services to those in need of medical attention. Clinics, hospitals, and community health services are all part of the health services sector. One healthcare facility crucial to enhancing the general state of public health is the hospital. In the healthcare sector, achieving patient satisfaction depends heavily on service quality. As a result of the growing degree of competition, hospitals are becoming more conscious of how important it is to give their patients the highest caliber of care. Aim: to investigate the impact of Service Quality (SQ) on Patient Satisfaction (PSAT). Methodology: a quantitative cross-sectional correlational study, a convenience sample of 380 in-patients receiving treatment at a governmental hospital, King Faisal Hospital in Saudi Arabia. Data was collected by using two questionnaires: Service Quality (SQ) and patient satisfaction (PSAT) with data analysis conducted using Amoss26 and SPSS26. Conclusion: The findings revealed Service Quality (SQ) positively influenced patient satisfaction. Limitation: Since there are fewer studies on Service Quality (SQ) in the healthcare sector than in manufacturing industries, this research substantially contributes to existing literature and merits additional study. Furthermore, this research offers significant perspectives for managers in the healthcare industry about strategic planning and decision-making procedures.